2020
DOI: 10.3390/su12104321
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Public Health Measures in Europe during the COVID-19 Pandemic

Abstract: SARS-CoV-2, a serious threat to sustainable development prospects, is spreading within countries at varying speeds, among other things depending on their population density, behavioural responses, cultural factors, personal hygiene practices and habits. This has led to significant variation in countries’ policy responses aimed at stemming the proliferation of the virus. Using crisp-set qualitative comparative analysis, we conducted a comparative study at the European level to study the performance of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Progression of CoV to severe pneumonia is directly related to advanced age, history of metabolic syndrome, smoking, and other chronic conditions such as cardiovascular disease [19]. Countries with a high percentage of advanced age and high population density in urban areas need to impose swiftly efficient measurements to reduce fatalities [19]. Primc et al analyzed the public health measures of European countries during the pandemic [19].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Progression of CoV to severe pneumonia is directly related to advanced age, history of metabolic syndrome, smoking, and other chronic conditions such as cardiovascular disease [19]. Countries with a high percentage of advanced age and high population density in urban areas need to impose swiftly efficient measurements to reduce fatalities [19]. Primc et al analyzed the public health measures of European countries during the pandemic [19].…”
Section: Resultsmentioning
confidence: 99%
“…Countries with a high percentage of advanced age and high population density in urban areas need to impose swiftly efficient measurements to reduce fatalities [19]. Primc et al analyzed the public health measures of European countries during the pandemic [19]. They concluded that qualitative development of the health care system and improving protective health conditions such as serum (25(OH)D) concentrations may be important for the control of COVID-19 [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations